Performance analysis of synthesized ZnO nanoparticles coated photovoltaic cell. (2020) - Kirthika, B.; Sekar, Sankar; Saravanan, S.; Shivasankaran, N.; Balan, A.V.; Kalirajan, M.
Abstract: Renewable energy is a source of clean, unlimited, and increasing competitive energy. In this work, the Zinc Oxide (ZnO) nanoparticles are synthesized by sol-gel techniques. ZnO nanoparticles were characterized by scanning electron microscope with EDAX and UV spectra. SEM image shows the spherical nanoparticles with a mean grain size of ∼110 nm. The ZnO nanoparticles were coated on the surface of the photovoltaic cell by using dip and RF sputtering techniques, respectively. The coating over the photovoltaic cell increases the efficiency of the photovoltaic cell of about 3.7% and 22% respectively.